The Infertility Trap: The Fertility Costs of Group-Living in Mammalian Social Evolution - Dunbar, Robin I. M.; Shultz, Susanne (Frontiers in Ecology and Evolution, 2021)
Mammal social groups vary considerably in size from single individuals to very large herds. In some taxa, these groups are extremely stable, with at least some individuals being members of the same group throughout their lives; in other taxa, groups are unstable with membership changing by the day. We argue that this variability in grouping patterns reflects a tradeoff between group size as a solution to environmental demands and the costs created by stress-induced infertility (the infertility trap). These costs are so steep that, all else equal, they will limit group size to 15-20 individuals. A species will only be able to live in larger groups if it evolves strategies that mitigate these costs. We suggest that mammals have opted for one of two options on how to solve this problem. One option (fission-fusion herds) is low cost but high risk; the other (bonded social groups) is risk-averse, but costly in terms of cognitive requirements.